Work design influences: A synthesis of multilevel factors that affect the design of jobs - Parker, Sharon; Van Den Broeck, A.; Holman, D. (2017)
High-quality work design is a key determinant of employee well-being, positive work attitudes, and job/organizational performance. Yet, many job incumbents continue to experience deskilled and demotivating work. We argue that there is a need to understand better where work designs come from. We review research that investigates the factors that influence work design, noting that this research is only a small fragment of the work design literature. The research base is also rather disparate, spanning distinct theoretical perspectives according to the level of analysis. To help integrate this literature, we use a framework that summarizes the direct and indirect ways in which work design is shaped by the higher-level external context (global/international, national, and occupational factors), the organizational context, the local work context (work group factors), and individual factors. We highlight two key indirect effects: first, factors affect formal decision-making processes via influencing managers’ work design–related motivation, knowledge, skills, and abilities (KSAs), and opportunities; and second, factors shape informal and emergent work design processes via influencing employees’ work design– related motivation, KSAs, and opportunities. By reviewing the literature according to this framework, we set the stage for more comprehensive theoretical development and empirical studies on the factors that influence work design.